Levosimendan in the Perioperative Period of Cardiac Surgery: a Case Report and Mini Review - Redant, Sébastien; Villet, Benoit; Attou, Rachid; Honore, Patrick M.; Bels, David De; Carbognani, Daniel (Cardiology and Cardiovascular Medicine, 2020)
The authors describe a case of a patient with severe ischemic heart disease who benefited from the combination of Levosimendan with intra-aortic balloon pump in the perioperative period of a triple coronary artery bypass graft. On this occasion, they review the literature on the benefits of levosimendan in this indication in terms of hemodynamics, renal function and mortality.